In and out of church: the moral arc of spiritual change in America - Tipton, Steven M. (Rowman & Littlefield, 2024)
"Why are Americans leaving church? Where have they gone, and how are they filling the gap? A leading sociologist of religion explains the shifting landscape of American denominational life through interviews and congregational case studies"--